Housing temperature influences exercise‐induced glucose regulation and expression of exerkines in mice - Zhijian Rao; Xue Geng; Peng Huang; Qiangman Wei; Shijie Liu; Chaoyi Qu; Jiexiu Zhao (Experimental Physiology)
Abstract The impact of housing temperature on exercise‐induced metabolic adaptations is not well understood, despite extensive research on the benefits of exercise for metabolic health. The aim of this study was to elucidate how housing temperatures influence the molecular responses and metabolic benefits of exercise in mice. Male C57BL/6N mice were housed at either room temperature (RT, 21°C) or in a thermoneutral environment (TN, 29°C) and subjected to either a 6‐week or acute exercise regimen. The results demonstrated that chronic exercise in TN conditions significantly improved glucose tolerance, whereas no such improvement was observed in RT conditions. Exercise reduced adipocyte size in inguinal and epididymal white adipose tissue in RT conditions, but no significant exercise‐induced browning of inguinal white adipose tissue was detected at either housing temperature. Additionally, housing temperature predominantly influenced key metabolic proteins in skeletal muscle, with exercise and temperature exhibiting interactive effects on glycogen synthase, Glut4 and Pgc‐1α. Moreover, the regulation of exerkines, including Fgf21, fetuin‐A, irisin, Gdf15, spexin and apelin, was temperature dependent after both long‐term and acute exercise. Notably, expression of Metrnl was consistently upregulated in skeletal muscle after long‐term exercise in both RT and TN environments, but was downregulated after acute exercise. These findings highlight that environmental temperature critically modulates the metabolic benefits of exercise and the expression of exerkines. The results of this study suggest that conventional RT conditions might obscure the full metabolic effects of exercise. We recommend the use of TN conditions in future research to reduce confounding factors and provide a more accurate assessment of the metabolic benefits of exercise.